Analisis Hubungan Komunikasi dan Budaya Perusahaan terhadap Kinerja Karyawan - Tony Margiyanto Adi (Neolectura, 2022)
The problem formulated from this writing is therelationship between organizational communication and organizational culture to the performance of employees of a company both jointly and partially and which variables have a dominant influence on employee performance. This type of research is quantitative research. Data collection in this study used questionnaires or questionnaires. This is in accordance with the research method used. In addition, the use of questionnaires is based on the consideration that respondents have an adequate level of education to be able to fill out the submitted questionnaires and in this study the data to be collected has been standardized. While the analysis tool used is multiple linear regression. The results showed a coefficient of determination (R2) value of 0.789. This means that organizational communication variables and organizational culture can explain the performance variable (Y) by 78.9%, while the remaining 21.1% is explained by other variables that are not included in this research model. Based on the table of calculated F values of 22.331 using a 2-sided test ? = 5%= 0.05 then from the distribution table F a value of 3.350 was obtained. By comparing the value of F count and F of the table then F count (22.331) > F of the table (3.350), then Ho is rejected and Ha is accepted. This means that there is a significant influence between free variables and bound variables.The partial s is obtained the communication variable (X1) has a calculated t value of (2.494) sig 0.019 > the table t value (1.703) then Ho is rejected and Ha is accepted. This means that there is a significant influence of partial communication variables on employee performance. And from partial testing the organizational culture variable (X2) has a calculated t value of (5.625) sig 0.000 > the table t value (1.703) then Ho is rejected and Ha is accepted. This means that there is a significant influence of partial Organizational Culture variables on employee performance. And this also shows that the variable of organizational culture is more dominant in influencing employee performance